Medical writing a guide for clinicians, educators, and researchers - Taylor, Robert B. (Springer New York, 2011)
Medical writing skills are crucial for clinicians, educators and researchers alike.  Whether you work in a busy practice or in an academic setting, Medical Writing will give you the know-how to translate observations and ideas into an article, report or book chapter that is ready for publication.  Dr. Robert B. Taylor, a distinguished leader in academic medicine, uses a clear, conversational style throughout this book to emphasize the personal enrichment that writing can bring.  Dr. Taylor draws from personal lessons learned while publishing two dozen medical books and several hundred papers to give valuable advice on writing:   -Review articles -Case reports -Editorials and letters to the editor -Book reviews -Book chapters -Reference books -Research protocols -Grant proposals -Research reports   Loaded with practical information, tips to help achieve publication of your work, and real world examples, Medical Writing can improve your skills, whether you are new to medical writing or a published author.